Dysfunction of intraflagellar transport-A causes hyperphagia-induced obesity and metabolic syndrome - Damon T. Jacobs; Luciane M. Silva; Bailey A. Allard; Michael P. Schonfeld; Anindita Chatterjee; George C. Talbott; David R. Beier; Pamela V. Tran (The Company of Biologists, 2016)
Primary cilia extend from the plasma membrane of most vertebrate cells and mediate signaling pathways. Ciliary dysfunction underlies ciliopathies, which are genetic syndromes that manifest multiple clinical features, including renal cystic disease and obesity. THM1 (also termed TTC21B or IFT139) encodes a component of the intraflagellar transport-A complex and mutations in THM1 have been identified in 5% of individuals with ciliopathies. Consistent with this, deletion of murine Thm1 during late embryonic development results in cystic kidney disease. Here, we report that deletion of murine Thm1 during adulthood results in obesity, diabetes, hypertension and fatty liver disease, with gender differences in susceptibility to weight gain and metabolic dysfunction. Pair-feeding of Thm1 conditional knock-out mice relative to control littermates prevented the obesity and related disorders, indicating that hyperphagia caused the obese phenotype. Thm1 ablation resulted in increased localization of adenylyl cyclase III in primary cilia that were shortened, with bulbous distal tips on neurons of the hypothalamic arcuate nucleus, an integrative center for signals that regulate feeding and activity. In pre-obese Thm1 conditional knock-out mice, expression of anorexogenic pro-opiomelanocortin (Pomc) was decreased by 50% in the arcuate nucleus, which likely caused the hyperphagia. Fasting of Thm1 conditional knock-out mice did not alter Pomc nor orexogenic agouti-related neuropeptide (Agrp) expression, suggesting impaired sensing of changes in peripheral signals. Together, these data indicate that the Thm1-mutant ciliary defect diminishes sensitivity to feeding signals, which alters appetite regulation and leads to hyperphagia, obesity and metabolic disease.